Optimasi Portofolio Saham Syariah Pada Saham IDX Sharia Growth Menggunakan Sharia-Compliant Capital Asset Pricing Model (SCAPM) - Azhara, Putri Indah; Subhan, Muhammad (Indo-MathEdu Intellectuals Journal, 2026)
The decline in global and national economic growth encourages investors to be more careful in making investment decisions, especially in the sharia capital market. This research aims to form an optimal sharia stock portfolio in the IDX Shariah Growth index using the Sharia-Compliant Capital Asset Pricing Model (SCAPM) method as a development of CAPM in accordance with sharia principles. This research is an applied research with a quantitative approach using secondary data in the form of the monthly closing price of IDX Shariah Growth shares for the period December 2022 to May 2025 as well as sukuk yield level data from the Ministry of Finance. The analysis is carried out by applying SCAPM to estimate expected returns, risks, and form an optimal portfolio, with the help of Microsoft Excel. The results of the study show that of the 30 stocks listed in the IDX Shariah Growth index, there are 10 stocks that meet the criteria as optimal stocks and can form an efficient portfolio. Among several portfolio alternatives, the portfolio with the highest number of returned stocks is chosen as the optimal portfolio because it produces the highest returns with still acceptable risk, as indicated by the highest Sharpe ratio value as well as performance above model expectations.